ARABIC LANGUAGE INSCRIPTIONS OF 17th - 18th CENTURIES ABOUT THE BUILDING THE MINARETS AND MOSQUE IN THE VILLAGE OF KHNOV - Zakariaev, Zamir Sahbanovic (History, Archeology and Ethnography of the Caucasus, 2018)
The article introduces into the scientific circulation the information about three Arabic language inscriptions dated back to the second half of the 17th c. - the first half of the 18th c. from the ancient Daghestan village Khnov. These epigraphic texts narrate about the building of cult muslim constructions of Khnov - minarets and Friday mosque. Khnov minarets haven’t preserved till now. The earliest one from the inscriptions under study is composed in 1080 year of the Hijrah (1669-70 year) when building the minaret and represents unique information about tragic consequence of the disastrous earthquake, which took place in the Eastern Caucasus in January of 1668. Two other inscriptions about the construction of minarets and Friday mosque are dated, correspondingly, with 1127/1715 and 1159/1746 years and contain information, which lacks in other historical sources. Building inscriptions inform about the names of the organizers and customers of the construction works, professional construction workers, composers and carvers of the texts, representatives of local muslim clergy and estate elite society. The published texts demonsrate the role and meaning of the epigraphic monuments in Arabic as the important source in history and culture of Daghestan. Arabic texts of the inscriptions with translation into Russian are supplemented with scientific comments.